Engineering EverQuest online gaming demands heavyweight data centers. - Kushner, D.
This paper describes how engineers keep a half million people from all over the world playing EverQuest, a best-selling computer game played over the Internet. Developed by Sony Online Entertainment, EverQuest has not only become a dominant force in the entertainment business but has also become a social phenomenon. It takes 13 data centers and more than 1500 servers located around the world to run EverQuest. As the game's audience expands and evolves, so does the architecture behind the scenes. To cope with these expansions, Sony has begun using blade servers and adopted just-in-time computing system. A Network Operations Center was also established to serve as Sony's 24-hour technical support. Sony has also begun efforts to adopt Wi-Fi and other wireless technologies into their future online and portable gaming offerings.
Keywords: EverQuest; Sony Online Entertainment; Wi-Fi technology; Blade servers; Computer games; Entertainment business; Graphics chips; Just in time computing; Logic circuitry; Online games; State-of-the-art microprocessors